COMPARISON BETWEEN USES OF CONTRACEPTIVE METHODS IN LHW COVERED AND LHW UNCOVERED AREAS - Alam, Muhammad Adeel; Zeb, Junaid; Manan, Zainab; Qureshi, Asfandyar; Mustajab, Mukarram; Junaid, Muhammad; Khan, Muhammad Aimal (Journal of Ayub Medical College Abbottabad, 2018)
Background: Family planning is of great importance in population dynamics as unregulated fertility negatively affects the economic stabilization of the country. Family planning is considered an effective way for the improvement of child and maternal health and reduces the maternal and perinatal morality. Total contraceptive prevalence rate (CPR) in Pakistan is 29% even of the fact that 97% Pakistani women know only one method of contraception. This study compares the contraceptive usage among LHW covered and LHW uncovered areas. Methods: This was a comparative cross-sectional study which was conducted in LHW covered and un covered areas in tehsil Takht Bai of district Mardan from August to December 2016. A sample of 102 families were selected randomly. All those females who were married, in reproductive ages (15-49 years) and were not pregnant were included in the study. Results: Out of total 102 females 44 (43.1%) were from LHW covered areas while 58 (56.9%) were from LHW uncovered areas. Overall knowledge about various birth control methods was more in uncovered areas, i.e., 71.4% than the covered ones which was 28.6%, p=0.67 and most ladies knew only about the contraceptive pills as compared to other methods. No statistical difference p=0.86 was found in usage of contraceptive methods among couples living in LHW covered and uncovered areas. Conclusion: This study highlights contraceptive usage and role of national program for family planning and primary health care in promotion of contraception. A lot more has to be done for the improvement of family planning services in the community. Keyword: contraception; family planning; LHW